Clinical and echocardiographic characteristics of cardioembolic stroke. (31st May 2019) - Ferkh, A.; Brown, P.; O'Keefe, E.; Zada, M.; Duggins, A.; Thiagalingam, A.; Altman, M.; Boyd, A.; Byth, K.; Kizana, E.; Denniss, A. R.; Thomas, L.
Abstract : Background and purpose: Ischaemic stroke frequently has a cardioembolic (CE) source. Clinical and echocardiographic parameters associated with CE stroke were evaluated. Methods: In all, 93 consecutive ischaemic stroke patients who underwent a transthoracic echocardiogram were retrospectively analysed; strokes were classified by TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria. Echocardiographic parameters related to CE stroke, including left atrial volumes and function, were compared to 73 healthy controls. Results: Of 93 patients (mean age 66.1 years, 56% male), nine (10%) had large artery atherosclerosis, 38 (41%) CE stroke, two (2%) small vessel disease, two (2%) other and 42 (45%) undetermined aetiology. Left atrial (LA) maximum volumes (LAVImax ) and minimum volumes (LAVImin ) were larger in the CE group than the non‐CE group (45 vs. 32 ml/m 2, 32 vs. 13 ml/m 2, respectively, P  < 0.001), whilst LA function indices including LA emptying fraction and LA function index (LAFI) were lower in the CE group (34% vs. 55%, and 0.12 vs. 0.35, respectively, P  < 0.001). Adjusting for clinical characteristics, LAFI ≤0.3 was an independent predictor of CE stroke (adjusted odds ratio 5.3, P  = 0.001). Additionally, LAVImax and LAVImin were larger (61 vs. 44 and 32 vs. 24 ml/m 2 respectively, P  < 0.01) and LAFI significantly lower (0.34 vs. 0.52, P  < 0.001) in the undetermined aetiology group versus healthy controls. Conclusions: Left atrial enlargement with reduced LA function was associated with CE stroke and LAFI was the best independent predictor. LA parameters were also altered in the undetermined aetiology group, suggesting an underlying LA myopathy in this subset.